Knock-In Mouse Models to Investigate the Functions of Opioid Receptors in vivo - Degrandmaison, Jade; Rochon-Haché, Samuel; Parent, Jean-Luc; Gendron, Louis (Frontiers in Cellular Neuroscience, 2022)
Due to their low expression levels, complex multi-pass transmembrane structure, and the current lack of highly specific antibodies, the assessment of endogenous G protein-coupled receptors (GPCRs) remains challenging. While most of the research regarding their functions was performed in heterologous systems overexpressing the receptor, recent advances in genetic engineering methods have allowed the generation of several unique mouse models. These animals proved to be useful to investigate numerous aspects underlying the physiological functions of GPCRs, including their endogenous expression, distribution, interactome, and trafficking processes. Given their significant pharmacological importance and central roles in the nervous system, opioid peptide receptors (OPr) are often referred to as prototypical receptors for the study of GPCR regulatory mechanisms. Although only a few GPCR knock-in mouse lines have thus far been generated, OPr are strikingly well represented with over 20 different knock-in models, more than half of which were developed within the last five years. In this review, we describe the arsenal of OPr (mu , delta- and kappa- opioid), as well as the opioid-related nociceptin/orphanin FQ (NOP) receptor knock-in mouse models that have been generated over the past years. We further highlight the invaluable contribution of such models to our understanding of the in vivo mechanisms underlying the regulation of OPr, which could be conceivably transposed to any other GPCR, as well as the limitations, future perspectives, and possibilities enabled by such tools.